2020
DOI: 10.3390/s20102939
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Lower Extremity Running Gait Kinematics with a Single Accelerometer: A Deep Learning Approach

Abstract: Abnormal running kinematics are associated with an increased incidence of lower extremity injuries among runners. Accurate and unobtrusive running kinematic measurement plays an important role in the detection of gait abnormalities and the prevention of injuries among runners. Inertial-based methods have been proposed to address this need. However, previous methods require cumbersome sensor setup or participant-specific calibration. This study aims to validate a shoe-mounted accelerometer for sagittal plane lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
99
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(103 citation statements)
references
References 48 publications
4
99
0
Order By: Relevance
“…The only double limb task used was a two-leg jump, and reported percent difference between the expected and predicted peak vertical knee force was 22.9%, highlighting the challenges of estimating double limb tasks. Gholami et al [ 29 ] used a single accelerometer on the foot combined with a convolutional neural network (CNN) to predict lower extremity kinematics during running gait, but did not predict kinetics. In relation to the work cited above, our project strategy specifically targeted the task and biomechanical variables of interest in post-ACLR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The only double limb task used was a two-leg jump, and reported percent difference between the expected and predicted peak vertical knee force was 22.9%, highlighting the challenges of estimating double limb tasks. Gholami et al [ 29 ] used a single accelerometer on the foot combined with a convolutional neural network (CNN) to predict lower extremity kinematics during running gait, but did not predict kinetics. In relation to the work cited above, our project strategy specifically targeted the task and biomechanical variables of interest in post-ACLR.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the use of inertial sensors combined with machine learning to predict biomechanics in musculoskeletal-injured populations has grown exponentially in recent years [ 19 ], serving as a promising interdisciplinary solution. This combined approach has proven successful for predicting knee-specific biomechanics for single-limb tasks including running, jump landing, and cutting [ 27 , 28 , 29 ]. However, these solutions have not specifically targeted double limb landing tasks, which have clinical relevance post-ACLR.…”
Section: Introductionmentioning
confidence: 99%
“…{r i | r i = p i −p i } where {p i } is the set of data points at specific gait events of the target signal (i.e., either at peak knee flexion during stance or peak hip flexion) andp i is the predicted value of p i in the regression. Following Gholami et al [5], in the calculation of RMSE, NRMSE, ST shown in Table 2, the peaks' positions indicated in Figure 2 were used, i.e., for the knee flexion and the maximum position in the hip flexion. For points in the curves were used.…”
Section: Standard Deviation Of the Set Of Residualsmentioning
confidence: 99%
“…MoCap is often combined with a treadmill to achieve a continuous walking trajectory for biomechanical research in a limited space [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. A treadmill provides a convenient experiment environment in terms of unlimited gait trackability under volume constraint and speed controllability.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, most of the gait data obtained through treadmill walking are analyzed based on gait cycle percentage. That is, each gait period from one heel strike to the next heel strike of the same foot is the time normalized as one gait cycle and the average and standard deviation of a physical quantity with respect to the gait cycle are used for the gait analysis [ 5 , 6 , 7 , 13 , 14 , 15 , 16 , 17 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%